Efeito ansiolítico do extrato etanólico de Pluchea sagittalis (Lam.) Cabrera, Asteraceae, em modelos comportamentais - Rodrigues, Sheyla Alves (2011)
Pluchea sagittalis (Lam.) Cabrera, Asteraceae, popularly known as quitoco, arnica, yerba lucera. Its stem and leaves are used in infusion to treat body pain, inflammation, nervous dyspepsia and hysteria. The purpose of this study was to isolate and identify the chemical constituents of the ethanol extract of leaves of P. sagittalis by checking the pharmacological potential of this extract, in particular on anxiety. The plant was collected in neighborhood Japãozinho, Aracaju - SE. The selected leaves were dried at 40 ° C with circulating air, ground and subjected to extraction with ethanol PA, soxleht. The extract was fractionated by column chromatography and analyzed by HPLC. The ethanol extract and fractions: aqueous, ethanol and acetone obtained were subjected to phytochemical screening and behavior pharmacological screening at a dose of 100 mg/kg, p.o. The motor activity of animals was found in the Open Field and Rota Rod test. The potential sedative hypnotic activity was evaluated in Barbiturate Induced Sleeping Time test. The anxiolytic activity was evaluated in Elevated Plus Maze test and Anticonvulsivant-induced for Pentilenotetrazol. In phytochemical analysis identified the presence of phenols, flavonoids, terpenes and steroids, was isolated a sesquiterpene. Pharmacological behavioral screening showed the potential depressant effect on the central nervous system (CNS) of all samples tested. In the Open Field, it was found that animals treated with a dose of 200 mg of crude ethanolic extract showed an increase in the number of walks and time shifting, with no observed change in motor coordination or muscle relaxation in Rota Rod doses 100 and 200 mg/kg proved to be inducing and potentiating barbiturate-induced sleep. The anxiolytic action was observed at a dose of 200 mg / kg in the labyrinth crux high. In addition to the protective effect against seizures induced by ptentilenotetrazol, doses of 100 and 200 mg/kg. It is concluded that the ethanolic extract of P. sagittalis presents anxiolytic action, with the possible participation of terpenes in this effect.